Pengembangan Model Sosialisasi Jaminan Kesehatan Nasional Melalui Peran Opinion Leader - Lestarini, Niken (Universitas Muhammadiyah Ponorogo, 2017)
This study aims to develop a model of socialization of the National Health Insurance through the role of Opnion Leader. The development of socialization model of National Health Insurance through the role of Opinion Leader is important because with the inclusion of communication technology in Rural areas has led to the emergence of social distance between opinion leaders (Opinion Leader) with the community. Although acknowledged that opinion leaders in Indonesia are still very instrumental in influencing the attitude and behavior of followers in the village. This research is also important to assist the Ponorogo Regency Government in implementing the National Health Insurance (JKN) Act organized by Social Security Administering Board (BPJS). This research is a continuation of research of Opnion Leader role which shows that its role is very high in socialization about Naional Health Insurance in the village. This research uses qualitative research paradigm. Data collection techniques used are in-depth interviews, observation and dukumentasi.Teknik Determination Informants using snowball technique, ie without determining the number of informants but based on information provided in accordance with the data required. Then the method of data analysis using Interactive Analysis Model. The results of research and discussion can be concluded that the Government set a target that in 2019 all Indonesian people have registered and have a card of National Health Insurance - Kartu Indonesia Sehat (JKN-KIS). So it has become a necessity for the socialization model that can really touch the people so that the target of the government can be achieved. Because JKN-KIS has become the thing that is needed by the society in carrying out their life to be healthy and prosperous and has been poured in Government regulation, the socialization model used belongs to the Represif socialization model. This socialization runs in one direction from one person to another. The implementation of the socialization of JKN-KIS should not only be the responsibility of the central and regional governments but the responsibility of all parties including the community as a whole. Through the role of Opinion Leader both formally and formally in the village community is needed because Opinion Leader is very close to the community and the place to ask related to all aspects of village life, in addition to understanding JKN-KIS there is awareness to become a participant of JKN-KIS both government-financed As well as pay dues independently.